1968
DOI: 10.1002/jsfa.2740191208
|View full text |Cite
|
Sign up to set email alerts
|

Persistence, penetration, and breakdown of chlorthiamid and dichlobenil herbicides in field soils of different types

Abstract: The persistence, penetration, and breakdown of the herbicides chlorthiamid (‘Prefix’, 2,6‐dichlorothio‐benzamide) and dichlobenil (‘Casoron’, 2,6‐dichlorobenzonitrile) have been studied in the field in clay, medium loam, sandy loam, and peat using applications of unincorporated granules and wettable powders at 9 kg/ha (active material). Conversion of chlorthiamid to dichlobenil was rapid in the soil. After 4 weeks, less than 3% remained of chlorthiamid that was applied to clay, medium loam, and sandy loam and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Ghlorthiamid is another herbicide which would have been decomposed sufficiently during the perfusion period to account for some of the apparent adaptation. This compound is not very resistant to microbial attack; it can be rapidly converted to dichlobenil within 4 weeks (Beynon & Wright, 1968). The subsequent disappearance of dichlobenil is much slower, the half-life ranging from 3 to 20 weeks (Beynon & Wright, 1968), and residues can be detected even up to a year (Slieets, Harris & Smith, 1968).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghlorthiamid is another herbicide which would have been decomposed sufficiently during the perfusion period to account for some of the apparent adaptation. This compound is not very resistant to microbial attack; it can be rapidly converted to dichlobenil within 4 weeks (Beynon & Wright, 1968). The subsequent disappearance of dichlobenil is much slower, the half-life ranging from 3 to 20 weeks (Beynon & Wright, 1968), and residues can be detected even up to a year (Slieets, Harris & Smith, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…This compound is not very resistant to microbial attack; it can be rapidly converted to dichlobenil within 4 weeks (Beynon & Wright, 1968). The subsequent disappearance of dichlobenil is much slower, the half-life ranging from 3 to 20 weeks (Beynon & Wright, 1968), and residues can be detected even up to a year (Slieets, Harris & Smith, 1968). However, as can be seen from Table 2, dichlobenil is about one-tenth as inhibitory to nitrification as chlorthiamid, and thus its rapid production from chlorthiamid during the perfusion period (28 days) could have accounted for the apparent adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…This paper deals with the methods of analysis and results of residue determinations on the 1970 fruit crop after harvest. Beynon & Wright (1968a) have described the rapid breakdown of chlorthiamid in the soil to dichlobenil and the subsequent formation of 2,6-dichlorobenzamide. Verloop & Daams (1970) have shown that uptake of 2,6-dichlorobenzamide from the soil can occur in woody plants and high concentrations of this breakdown product in the leaves are associated with marginal chlorosis.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes able to degrade BAM or dichlobenil have been isolated from soil surface, where BAM has been persistent, slowly or fast degraded by microbes after the exposure to dichlobenil (Beynon and Wright 1968;Clausen et al 2007;Holtze et al 2007a, b;Miyazaki et al 1975;Montgomery et al 1972;Verloop 1972;Vosáhlová et al 1997). The long-term exposure to herbicides generally improves the ability of soil microbes to degrade these compounds.…”
Section: Introductionmentioning
confidence: 98%